The involvement of metal-to-CO charge transfer and ligand-field excited states in the spectroscopy and photochemistry of mixed-ligand metal carbonyls. A theoretical and spectroscopic study of [W(CO)(4)(1,2-ethylenediamine)] and [W(CO)(4)(N,N'-bis-alkyl-1,4-diazabutadiene)] - Zális, Stanislav; Farrell, Ian R; Vlcek, Jr, Antonín (Journal of the American Chemical Society, 2003)
A new interpretation of the electronic spectroscopy, photochemistry, and photophysics of group 6 metal cis-tetracarbonyls [M(CO)(4)L(2)] is proposed, that is based on an interplay between M --> L and M --> CO MLCT excited states. TD-DFT and resonance Raman spectroscopy show that the lowest allowed electronic transition of [W(CO)(4)(en)] (en = 1,2-ethylenediamine) has a W(CO(eq))(2) --> CO(ax) charge-transfer character, whereby the electron density is transferred from the equatorial W(CO(eq))(2) moiety to pi orbitals of the axial CO ligands, with a net decrease of electron density on the W atom. The lowest, emissive excited state of [W(CO)(4)(en)] was identified as a spin-triplet W(CO(eq))(2) --> CO(ax) CT excited state both computationally and by picosecond time-resolved IR spectroscopy. This state undergoes 1.5 ps vibrational relaxation/solvation and decays to the ground state with a approximately 160 ps lifetime. The nu(CO) wavenumbers and IR intensity pattern calculated by DFT for the triplet W(CO(eq))(2) --> CO(ax) CT excited state match well the experimental time-resolved spectrum. For [W(CO)(4)(R-DAB)] (R-DAB = N,N'-bis-alkyl-1,4-diazabutadiene), the W(CO(eq))(2) --> CO(ax) CT transition follows in energy the W --> DAB MLCT transition, and the emissive W(CO(eq))(2) --> CO(ax) CT triplet state occurs just above the manifold of triplet W --> DAB MLCT states. No LF electronic transitions were calculated to occur in a relevant energetic range for either complex. Molecular orbitals of both complexes are highly delocalized. The 5d(W) character is distributed over many molecular orbitals, while neither of them contains a predominant metal-ligand sigma 5d(W) component, contrary to predictions of the traditional ligand-field approach. The important spectroscopic, photochemical, and photophysical roles of M(CO(eq))(2) --> CO(ax) CT excited states and the limited validity of ligand field arguments can be generalized to other mixed-ligand carbonyl complexes.